Research on the Influence of Near-Fault Round Motion Pulse Characteristics on Seismic Response of Base-Isolated Structures. Issue 1 (August 2020) - Wang, Yanan; Liu, Yonghui; Wang, Hairong
Abstract: The time-frequency distribution of near-fault pulsed ground motion is different from that of ordinary ground motion because of its long period, short duration and high energy acceleration pulse effect, which has a significant influence on the structure with long natural vibration period, such as isolated structure. In this paper, the pulse characteristics of near-fault seismic records and their influence on the seismic response of isolated layer and superstructure are studied by selecting near-fault pulsed seismic records and far-field common seismic records as external excitation. The results show that compared with the far-field ordinary seismic waves, the 3D Hilbert amplitude spectrum of near-fault pulsed seismic waves is distributed in the low frequency region and the middle and late time domain, and the amplitude is also larger. The first natural vibration frequency of the isolated structure is located at the peak of the power spectrum of the near fault pulse wave, which makes the seismic response of the isolated structure in the near fault pulse type seismic record obviously larger than that in the far field common seismic record. The intensity indexes Sa(T1 ) and Sd(T1 ) of near-fault pulsed ground motion are greater than those of ordinary ground motion. The relationship between them and structural seismic response should be studied in depth.